Russell Gillen

2021-12-16

Factor the quadratic polynomials.

${x}^{2}-4x-12$

MoxboasteBots5h

Beginner2021-12-17Added 35 answers

The given quadratic polynomial is ${x}^{2}-4x-12$ .

It is factored as follows.

${x}^{2}-4x-12={x}^{2}-6x+2x-12$

=x(x-6)+2(x-6)

=(x+2)(x-6)

It is factored as follows.

=x(x-6)+2(x-6)

=(x+2)(x-6)

Joseph Fair

Beginner2021-12-18Added 34 answers

The given equation is:

${x}^{2}-4x-12$

$\Rightarrow {x}^{2}-4x=12$

Thus,

${x}^{2}-4x=12$

$\Rightarrow {x}^{2}-4x-12=0$

The product of the second degree term and the constant is$-12{x}^{2}$ . Factors of $-12{x}^{2}$ that sum to -4x are -6x and 2x. Thus,

Factorizing which we get,

${x}^{2}-4x-12=0$

$\Rightarrow {x}^{2}-6x+2x-12=0$

$\Rightarrow x(x-6)+2(x-6)=0$

$\Rightarrow (x-6)(x+2)=0$

The required values of x are 6 and -2.

Thus,

The product of the second degree term and the constant is

Factorizing which we get,

The required values of x are 6 and -2.